2006
DOI: 10.1007/s11071-006-0744-z
|View full text |Cite
|
Sign up to set email alerts
|

Stability in Shells

Abstract: This paper charts the various ways in which a close working relationship with Michael Thompson, during our early years within the Stability Research Group at UCL, came to have such a profound influence on the direction of my own research activities. In particular, his fascination with energy and its use in providing a systematic framework for looking at the initial post-buckling of systems was especially contagious, opening up for me new ways of approaching the interpretation of shell buckling. In a sense my o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…The above reported studies have suggested that the axial load buckling behaviour of the isotropic cylinder can be viewed as simply a rather special case of the behaviour displayed by shells constructed from orthotropic fibre-reinforced composite materials. This echoes earlier suggestions that the behaviour of rib-reinforced cylinders could equally be seen as a generalization of the behaviour of the isotropic cylinder [16,3132]. But what recent work exploiting the potential of ‘high-fidelity’ numerical experimentation shows, when interpreted within the framework of classical and its RS extension, is that this behaviour can be presented in a form of potential importance for design.…”
Section: Towards a Systematic Design Approachsupporting
confidence: 82%
“…The above reported studies have suggested that the axial load buckling behaviour of the isotropic cylinder can be viewed as simply a rather special case of the behaviour displayed by shells constructed from orthotropic fibre-reinforced composite materials. This echoes earlier suggestions that the behaviour of rib-reinforced cylinders could equally be seen as a generalization of the behaviour of the isotropic cylinder [16,3132]. But what recent work exploiting the potential of ‘high-fidelity’ numerical experimentation shows, when interpreted within the framework of classical and its RS extension, is that this behaviour can be presented in a form of potential importance for design.…”
Section: Towards a Systematic Design Approachsupporting
confidence: 82%
“…The lower bound is found when the membrane energy part is eliminated. In a series of papers for several cases [25,[62][63][64], the merits of the method were demonstrated. It was also shown [65] that the lower bounds determined by a slightly modified form of this method agree very well with experimental lower bounds.…”
Section: Postbuckling Behaviour and Lower Boundsmentioning
confidence: 99%
“…The Reduced Energy Analysis (REA) has been described by Croll and co-workers [27,28], and a slightly different formulation was given in Ref. [37].…”
Section: Reduced Energy Analysis (Rea)mentioning
confidence: 99%
“…The best readings reviewing the lower bound approach were presented by Croll as a design methodology [27,28] in which details of the motivations and achievements at each stage are discussed in an amenable way.…”
Section: Introductionmentioning
confidence: 99%